Plasma vitamin D deficiency is associated with poor sleep quality and night-time eating at mid-pregnancy in Singapore - Cheng, Tuck Seng (2018)
Plasma 25-hydroxyvitamin D (25OHD) deficiency, poor sleep quality, and night-time eating, have been independently associated with adverse pregnancy outcomes, but their inter-relationships are yet to be evaluated. We aimed to investigate the associations between maternal plasma 25OHD status and sleep quality and circadian eating patterns during pregnancy. Data on pregnant women (n = 890) from a prospective cohort (Growing Up in Singapore Towards healthy Outcomes) were analyzed. Plasma 25OHD concentration was measured, while the Pittsburgh sleep quality index (PSQI) and 24-h dietary recall were administered to women at 26–28 weeks’ gestation. Plasma 25OHD status was defined as sufficient (>75 nmol/L), insufficient (50–75 nmol/L), or deficient (<50 nmol/L). Poor sleep quality was defined by a total global PSQI score >5. Predominantly day-time (pDT) and predominantly night-time (pNT) were defined according to consumption of greater proportion of calories (i.e., >50%) from 07:00–18:59 and from 19:00–06:59, respectively. After adjustment for confounders, women with plasma 25OHD deficiency had higher odds of poor sleep quality (odds ratio (OR) 3.49; 95% confidence interval (CI) 1.84–6.63) and pNT eating (OR: 1.85; 95% CI 1.00–3.41) than those who were 25OHD sufficient. Our findings show the association of maternal plasma 25OHD deficiency with poor sleep quality and pNT eating at mid-pregnancy.